Diagnosing primary ciliary dyskinesia: an international patient perspective - Behan, Laura (European Respiratory Society, 2016)
Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterised by progressive sino-pulmonary disease, with symptoms starting soon after birth. A European Respiratory Society (ERS) Task Force aims to address disparities in diagnostics across Europe by providing evidence-based clinical practice guidelines. We aimed to identify challenges faced by patients when referred for PCD diagnostic testing.